Work-From-Home experience and its impact on employees' integrity / Siti Nur Izzah Anuar, Jafni Jamaluddin and Zurina Md Nen - Anuar, Siti Nur Izzah; Jamaluddin, Jafni; Md Nen, Zurina (2021)
Remote working is a working method that helps in executing work outside the traditional office environment. Globally, remote working existed even before the 1980s where management was entitled to work remotely by only 10%. However, with the outbreak of Corona Virus Disease 2019 (Covid-19), remote working has become a new normal. Large tech employers such as Apple, Google, Microsoft, and Facebook were among the first to work up remote work plans for many of their employees around the globe (www.shrm.org). As Covid- 19 continues to spread and vaccination was not available in early 2020, work from home (WFH) appears as the best remote working option for many countries throughout the world following the decision for total lockdown. International Labor Organization (2020) defines WFH as a working arrangement in which workers fulfill the essentials of his/her job responsibilities at home with the assistance of information and communication technology (ICT). Malaysia is no exception. To contain the spread of disease, the Malaysian Government announced Movement Control Order (MCO) in March 2020 (Prime Minister Office, 2020). The order includes the closure of public and private premises except for several essential services. Consequently, many workers are forced to shift to WFH basis. When the government decided to tighten MCO due to the existence of more aggressive new variants with high infection rates, the WFH policy make compulsory WFH for 40% of private-sector employees and 80% of government employees (Public Service Department, (PSD) 2020), affecting 750,000 government staff and about 6.1 million private-sector workers (Ministry of Defense, 2021). While adapting to WFH basis, there is increasing concern on whether employees have been successfully fulfilling their responsibilities when working from home. With considerably reduced capacity for direct supervision of staff which may pose a high risk of unethical behavior, the integrity of remote workers has become a topic of debate. On this basis, this paper is written to examine employees' experience of working from home and its impacts on employees' integrity.